The brave new world: imperfect information, segregation costs, and genetically modified organisms - Charles B. Moss; Troy G. Schmitz; Andrew Schmitz (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
The introduction of genetically modified (GM) crops in the mid 1990s appeared to be the latest in a string of technological innovations in agriculture. However, consumer resistance, particularly in Europe has limited the sector's enthusiasm. One response to the limited enthusiasm has been the emergence of segregated markets for GM and non-GM products. These separated markets reduce economic welfare because they require additional costs in the marketing system. Offsetting these segregation costs, however, the introduction of GM technologies offers increased economic welfare through reduced commodity prices for consumers who are indifferent to the presence of GM traits and increased profits to producers who adopt GM technologies. This study develops the combinations of segregation costs and increased supplies that leave societal surplus unchanged. Any GM technology that yields a larger increase in supply for any segregation cost depicted in this relationship meets the compensation principle and, thus, improves societal welfare. In this case, market based adoption of these technologies improve economic surplus. On the other hand, technologies that yields less increase in supply for any segregation cost reduces societal welfare. Under this scenario, market based adoption will not be welfare improving and, hence, government regulation may be required. – – Dieser Beitrag überprüft die Wohlstandseffekte, die durch die Einführung von Pflanzen mit gentechnisch modifizierten Organismen (GVO-Pflanzen) sowohl für die Erzeuger von GVO- und Nicht-GVO-Pflanzen, als auch für die Verbraucher von GVO-und Nicht-GVO-Pflanzen entstehen. Es wird ein partielles Gleichgewichtsmodell der Märkte für GVO- und Nicht-GVO-Pflanzen formuliert, das Kosten der Markttrennung einbezieht, wie auch die Angebotsverschiebung, die durch die Einführung der GVO-Pflanzen verursacht wird. Anschließend wird das Modell verwendet, um die Kombinationen von Kosten der Markttrennung und von Angebotsverschiebungen zu bestimmen, die entweder eine Verbesserung oder eine Verschlechterung der gesellschaftlichen Wohlfahrt mit sich bringen. In den Fällen, in denen durch die Einführung der GVO-Pflanzen der Wohlstand steigen würde, kann eine staatliche Aktivität notwendig werden, um die potenziellen Verlierer durch die Einführung der GVO-Pflanzen zu kompensieren. (Quelle: Verlag)
Keywords: 330; Lebensmittel; Gentechnik; Marktsegmentierung; Unvollkommene Information; Pareto-Optimum; Wohlfahrtsanalyse; Lebensmitteltechnik